РАЗЛИЧИТЕ ВРСТЕ САЈБЕР ПРЕТЊИ - Luknar, Ivana; Jovanović, Filip (Serbian political thought, 2024)
Security of the Internet and online communication has become an essential challenge in contemporary world. Paper discusses different types of cyber threats: cyber-attack, cyberterrorism and cybercrime. Individuals, companies and the states rely their communication and daily functioning on information and communication technologies (ICT). The purpose of the study is to highlight importance of the ICT safety use by pointing to seriousness of the cyber threats. The main methods applied in paper to examine published scientific materials are: inductive and deductive method, analytical and synthesis method, hypothetical-deductive method and method of content analysis. Results of the study indicate need for actively dealing with cyber threats. The intent of this study is both to inform and raise awareness of cyber threats within the communities. Findings of the study contribute to the broader knowledge in research area.
Keywords: cyber threats; cyber-attack; cyberterrorism; cybercrime; cybersecurity; cyber defense